The nature of Buddhist ethics - Keown, Damien (New York, NY : Palgrave, 2002)
In this book the author considers data from both early and later schools of Buddhism in an attempt to provide an overall characterisation of the structure of Buddhist ethics. The importance of ethics in the Buddha's teachings is widely acknowledged, but the pursuit of ethical ideals has up to now been widely held to be secondary to the attainment of knowledge. Drawing on the Aristotelian tradition of ethics Dr. Keown argues against this intellectualization of Buddhism.
Revision of author's thesis (Ph. D.)--Oxford. Includes bibliographical references and index.
Keywords: Buddhist ethics